Convergence, Shocks and Poverty - Chris Elbers; Jan Willem Gunning; Bill Kinsey (Tinbergen Institute, 2002)
Using a unique panel data set for rural households in Zimbabwe we estimate amicroeconomic model of growth under uncertainty, a stochastic version of the Ramsey modelwith livestock as the single asset. We use the estimation results in simulation experiments(over a 20-year period) to quantify the importance of convergence, household fixed effectsand shocks. First, we find powerful convergence. In the absence of shocks and withouthousehold fixed effects there is rapid growth over the period (5.6% growth p.a. in percapita assets) even though there is no technical progress. The process of adjusting thecapital stock (livestock) to its steady state value is - as expected - strongly equalising:the coefficient of variation (across households) of livestock ownership falls from 78% to6%. Secondly, when we allow for household fixed effects - the case of conditionalconvergence - the aggregate growth rate is very similar but inequality remains highthroughout the period.Finally, we find that shocks have strong and persistent effects. In this model shocksaffect aggregate growth both ex ante and ex post. These effects are strong: shocks reduceaggregate growth over the period by a fifth and increase inequality substantially.
Keywords: O12; D91; 330; convergence; poverty dynamics; growth under uncertainty; Wachstumstheorie; Wirtschaftswachstum; Schock; Theorie